2009
DOI: 10.1080/08860220902963558
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Plant-Derived Oleanolic Acid in Streptozotocin-Induced Diabetic Rats

Abstract: Previous studies from our laboratories indicate that the antidiabetic effects of Syzygium cordatum (Hochst.) [Myrtaceae] leaf extract in streptozotocin-induced diabetic rats may be attributed in part to mixtures of triterpenes, oleanolic acid (3ß-hydroxy-olea-12-en-28-oic acid, OA) and ursolic acid (3ß -hydroxyl-urs-12-en-28-oic acid, UA). For the bioactive compounds to have potential in diabetes management, they should alleviate or prevent complications of diabetes mellitus, kidney function, and cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…The solvents were removed under reduced pressure to give corresponding residues of hexane-solubles, dichloromethane-solubles, ethyl acetatesolubles (EAS), and methanol-solubles. Recrystallization of EAS which had been previously shown to contain OA ursolic acid/methyl maslinate/methyl corosolate 3,15 with ethanol yielded pure OA, whose structure was confirmed by spectroscopic analysis using 1D and 2D, 1 H and 13 C nuclear magnetic resonance techniques. Preliminary studies indicated that the S. aromaticum-isolated OA and commercial OA were similar and hence the plantextracted OA was used in the experiments as it costs less.…”
Section: Isolation Of Oamentioning
confidence: 87%
See 3 more Smart Citations
“…The solvents were removed under reduced pressure to give corresponding residues of hexane-solubles, dichloromethane-solubles, ethyl acetatesolubles (EAS), and methanol-solubles. Recrystallization of EAS which had been previously shown to contain OA ursolic acid/methyl maslinate/methyl corosolate 3,15 with ethanol yielded pure OA, whose structure was confirmed by spectroscopic analysis using 1D and 2D, 1 H and 13 C nuclear magnetic resonance techniques. Preliminary studies indicated that the S. aromaticum-isolated OA and commercial OA were similar and hence the plantextracted OA was used in the experiments as it costs less.…”
Section: Isolation Of Oamentioning
confidence: 87%
“…1,2 However, increasing evidence suggests that OA possesses hypoglycemic properties and may also have beneficial effects on some processes associated with impaired kidney function in diabetes. 3,4 Indeed, OA appears to reverse the previously reported inability of the kidney to excrete Na þ in streptozotocin (STZ)-induced diabetic rats. 5 These findings suggest that OA may be influencing transport processes in the proximal tubule, the site for the reabsorption of approximately two-thirds of the Na þ that enters the tubular fluid by glomerular filtration.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…[71] Cornus officinalis + ↓ Kidney ROS [72] Gongronema latifolium + ↑ Superoxide dismutase (SOD), glutathione peroxidase [73] Rheum emodi − (GPx), reduced glutathione (GSH), catalase, etc. [74] Vigna angularis − Renoprotection [75] Helicrysium ceres + Amelioration of renal function [76] Oleanolic acid (Syzygium cordatum) + ↑ GFR [77] Sclerocarya birrea + ↓ Plasma urea and creatinine concentrations [19] Opunthia megacantha + ↓ Urinary protein concentration [20] Persea americana + [78] Jawarishi Zarooni Sada (a polyherbal unani formulation) − [79] Corni fructus + Maintenance of kidney structure [80] Curcumin (Curcumin longa) + ↓ Kidney levels of RAGE, AGE, TGF-ß 1 [81] Allium sativum and Zingiber officinale + ↓ Extra-cellular matrix proteins (e.g., fibronectin) [82] Momordica charantia + ↓ Renal hypertrophy [26] Coptis chinensis and Phellodendron amurense + [49] Hypoxis hemerocallidea + Reno-toxic effects [66] Opunthia megacantha + ↓GFR↑ serum urea and creatinine concentrations [83] …”
Section: Resultsmentioning
confidence: 99%